Cover Image. Issue 4 (25th March 2018) - Chu, Shanshan; Tan, Lingling; Liu, Chanchan; Peng, Huasheng; Duan, Haiyan; Huang, Luqi
Abstract : On the cover: The cover image, by Shanshan Chu et al., is based on the Research Article Growth rings in roots of medicinal perennial dicotyledonous herbs from temperate and subtropical zones in China, DOI:10.1002/jemt.22987 .